The friendly foal - Daniels, Lucy; Ripper, Georgie (Hodder Children's London, 2003)
Mandy's friend Helen is very excited. She has a new foal called Fern, who just loves to play! But Helen's about to move house, and she's worried that Fern will be lonely without lots of friends around. Then Mandy has a brilliant idea